2023
DOI: 10.1136/bmjopen-2023-077243
|View full text |Cite
|
Sign up to set email alerts
|

Placebo and nocebo effects and mechanisms associated with pharmacological interventions: an umbrella review

Elisa Frisaldi,
Aziz Shaibani,
Fabrizio Benedetti
et al.

Abstract: ObjectivesThis review aimed to summarise the existing knowledge about placebo and nocebo effects associated with pharmacological interventions and their mechanisms.DesignUmbrella review, adopting the Assessment of Multiple Systematic Reviews 2 tool for critical appraisal.Data sourcesMEDLINE/PubMed, Scopus, Web of Science, PsycINFO, Cochrane Central Register of Controlled Trial were searched in September 2022, without any time restriction, for systematic reviews, narrative reviews, original articles. Results we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 116 publications
1
5
0
Order By: Relevance
“…Indeed, a dose-response relationship was found in a 10 km TT test, with cyclists reducing performance by 1.4% when they believed they had ingested a placebo and increasing performance by 1.3% when they believed they had ingested 4.5 mg/kg caffeine and 3.1% when they believed they had ingested 9.0 mg/kg caffeine [22]. According to our data and other previous research, the placebo effect could improve endurance performance by around ≈2-3%, and this could be explained by a variety of factors, such as fatigue endurance, pain tolerance, and motivation [1].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Indeed, a dose-response relationship was found in a 10 km TT test, with cyclists reducing performance by 1.4% when they believed they had ingested a placebo and increasing performance by 1.3% when they believed they had ingested 4.5 mg/kg caffeine and 3.1% when they believed they had ingested 9.0 mg/kg caffeine [22]. According to our data and other previous research, the placebo effect could improve endurance performance by around ≈2-3%, and this could be explained by a variety of factors, such as fatigue endurance, pain tolerance, and motivation [1].…”
Section: Discussionsupporting
confidence: 71%
“…The placebo effect (i.e., an improvement derived from something that has no effect by itself) has been broadly studied in medicine and psychology in various clinical conditions [ 1 ]. In recent decades, an increasing interest has emerged in sports sciences research, where previous reviews have found small to moderate exercise performance improvements [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“… Prior Expectations and Learning Personality and individual differences Communication of information and patient-physician relationship 42. E. Frisaldi et al (2023) To summarize the current understanding of placebo and nocebo effects linked to pharmacological interventions, along with an exploration of their underlying mechanisms. N = 158 312 The characterization of mechanisms associated with placebo and/or nocebo effects in various medical conditions was demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, previous positive experiences may enhance placebo analgesic effects, while negative experiences can induce nocebo effects ( Colloca and Benedetti, 2016 ). This category receives additional validation from a recent umbrella review conducted by Frisaldi et al (2023) . Their extensive analysis has demonstrated that, in the context of nocebo effects, the manipulation of expectations, conditioning, or a combination of both has proven effective in eliciting nocebo responses across diverse domains, such as pain perception, skin dryness, nausea, and cognitive performance ( Frisaldi et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation